Strategic management for Iris potato famine fungus - Arora, R K (Indian Horticulture, 2019)
Global losses due to P. infestans have been estimated to $ 12 billion per annum. Of which, the losses in developing countries have been estimated around • 10 billion per annum. It cuts global potato production by around 15%. In India, late blight occurs every year in north-western hills of Himachal Pradesh, Uttarakhand, north-eastern hills of Meghalaya and the south Indian hills. It occurs in severe form once in 3-4 years in Indo-Gangetic plains comprising Punjab, Uttar Pradesh, Bihar and West Bengal, which is major potato-producing area, contributing to 85–90% of the total potato production in the country, and cause huge losses. Yield losses in India due to late blight in blight years ranges from 19–65% in eastern hills, 11–74% in north-western hills, 10–75% in eastern plains, 20–40% in north-western plains and 31–39% in southern hills.